A Conceptual History of Gifted Education - Gil Jr., Tyrone O. (LPPI Yayasan Almahmudi bin Dahlan, 2026)
This paper traces the historical evolution of giftedness conceptualization from ancient philosophical foundations to modern psychometric paradigms, delineating shifts from demystification (scientific scrutiny of divine/mystical traits) to identification and emerging transactional models emphasizing context and equity. Employing a narrative literature review of primary texts and secondary analyses, it examines philosophical founders—Plato's meritocratic